Césure et sublime - Bieńczyk, Marek (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
Having written The Joke, Kundera changed the modus vivendi of the novel’s narrator who, with time, became a separate protagonist. This is connected with the appearance of the ellipsis as the main plot device, which is not yet present in The Joke. This change in the way of narrating represents another and, perhaps, a deeper dividing line in Kundera’s writing than switching to another language (from Czech to French), the change of the setting (from Czechoslovakia to Western countries) and the change of the political system (from communist to ‘imagological’) as an instrument of oppression.